Guided graded Exercise Self-help for chronic fatigue syndrome: patient experiences and perceptions. Issue 3 (30th January 2020) - Cheshire, Anna; Ridge, Damien; Clark, Lucy; White, Peter
Abstract: Purpose : This study explored patient experiences of Guided graded Exercise Self-help (GES) delivered as part of a randomised controlled trial for people with chronic fatigue syndrome/myalgic encephalomyelitis. The trial found that GES was better than specialist medical care at reducing fatigue and improving physical functioning. Methods : Semi-structured interviews were conducted with patients reporting improvement ( n = 9) and deterioration ( n = 10), and analysis involved thematic "constant comparison." Results : The improved group described more facilitators to doing GES, and were more likely to describe high levels of self-motivation, whereas the deteriorated group described more barriers to GES (including worse exacerbation of symptoms after GES, greater interference from comorbid conditions, and obstacles to GES in their lives), and had been ill for longer. Having the capacity to do GES was important; of note, those with relatively lower levels of functioning sometimes had more time and space in their lives to support their GES engagement. We identified an important "indeterminate phase" early on, in which participants did not initially improve. Conclusions : GES may be improved by targeting those most likely to improve, and teaching about the indeterminate phase. Implications for rehabilitation: Using the Guided Exercise Self-help booklet alone is unlikely to be sufficient to support patients through Guided Exercise Self-help successfully. Additional guidance from skilled physiotherapists/health professionals who demonstrate an understanding of what it is like to cope with chronic fatigue syndrome/myalgic encephalomyelitis is also important. Those using Guided Exercise Self-help may need additional support through a commonly experienced "indeterminate phase" – an initial phase in the programme where few benefits, along with various challenges associated with increasing activity, are experienced. Individuals who have been ill with chronic fatigue syndrome/myalgic encephalomyelitis for a relatively longer period of time and/or have additional comorbid conditions may benefit from more bespoke therapies with greater health professionals input, delivered by appropriate therapists.